Analyzing cost efficient production behavior under economies of scope: a nonparametric methodology - Laurens Cherchye; Bram de Rock; Frederic Vermeulen (Institute for the Study of Labor (IZA), 2006)
In designing a production model for firms that generate multiple outputs, we take as a starting point that such multi-output production refers to economies of scope, which in turn originate from joint input use and input externalities. We provide a nonparametric characterization of cost efficient behavior under these conditions, and subsequently institute necessary and sufficient conditions for data consistency with such efficient behavior that only include observed firm demand and supply data. We illustrate our methodology by examining the cost efficiency of research programs in Economics and Business Management faculties of Dutch universities. This application shows that the proposed methodology may entail robust conclusions regarding cost efficiency differences between universities within specific specialization areas, even when using shadow prices to evaluate the different inputs
Keywords: 330